2017
DOI: 10.1128/aac.02291-16
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Antimalarial Dose Regimens for Sulfadoxine-Pyrimethamine with or without Azithromycin in Pregnancy Based on Population Pharmacokinetic Modeling

Abstract: Optimal dosing of sulfadoxine-pyrimethamine (SP) as intermittent preventive treatment in pregnancy remains to be established, particularly when coadministered with azithromycin (AZI). To further characterize SP pharmacokinetics in pregnancy, plasma concentration-time data from 45 nonpregnant and 45 pregnant women treated with SP-AZI (n ϭ 15 in each group) and SP-chloroquine (n ϭ 30 in each group) were analyzed. Population nonlinear mixed-effect pharmacokinetic models were developed for pyrimethamine (PYR), sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…Potential confounders not included in the original modeling reduced, but did not eliminate, between‐site differences in pharmacokinetic parameters. For sulfadoxine, there was an overall threefold higher clearance during pregnancy vs. that after delivery, consistent with other available data2, 3, 4 and reflecting pregnancy‐associated physiological changes 1. Pyrimethamine clearance was, by contrast, 18% lower in pregnancy compared with the postpartum period, with a reduced area under the plasma concentration‐time curve (AUC) after delivery 1…”
Section: Figuresupporting
confidence: 87%
See 4 more Smart Citations
“…Potential confounders not included in the original modeling reduced, but did not eliminate, between‐site differences in pharmacokinetic parameters. For sulfadoxine, there was an overall threefold higher clearance during pregnancy vs. that after delivery, consistent with other available data2, 3, 4 and reflecting pregnancy‐associated physiological changes 1. Pyrimethamine clearance was, by contrast, 18% lower in pregnancy compared with the postpartum period, with a reduced area under the plasma concentration‐time curve (AUC) after delivery 1…”
Section: Figuresupporting
confidence: 87%
“…This suggests strongly that lactating women are not metabolically equivalent to nonpregnant women in the case of pyrimethamine. The reduced pyrimethamine clearance in pregnancy relative to that postpartum, as reported by de Kock et al .,1 does not, therefore, contradict other studies using nonpregnant women as the comparator group that showed increased pyrimethamine clearance and a lower AUC 3, 4…”
Section: Figurementioning
confidence: 58%
See 3 more Smart Citations